All-Arthroscopic Autologous Matrix-Induced Chondrogenesis-Aided Repair of a Patellar Cartilage Defect Using Dry Arthroscopy and a Retraction System - Sadlik, Boguslaw; Puszkarz, Mariusz; Kosmalska, Lidia; Wiewiorski, Martin (The Journal of Knee Surgery, 2017)
The technique of all-arthroscopic autologous matrix-induced chondrogenesis (AMIC)-aided repair of patellar cartilage lesions using a retraction system and dry arthroscopy has been recently described. We report the first clinical and radiological data at a short-term follow-up. Twelve patients underwent AMIC-aided cartilage repair for a patellar lesion. All steps of the procedure were performed arthroscopically, which include the use of an intra-articularly placed retraction plate for distraction of the patellofemoral joint and evacuation of saline solution for collagen matrix insertion and fixation. Clinical assessment performed before surgery and at a mean follow-up time of 38 months (range: 24–70) included the following scores: Knee Injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC), and visual analog scale (VAS). Magnetic resonance imaging was performed at the follow-up examination, including the magnetic resonance observation of cartilage repair tissue (MOCART) score. The mean KOOS and IKDC scores increased significantly (p < 0.01) from 50.3 and 37.4 points preoperatively to 90.1 and 79.4 postoperatively. The VAS score decreased from 7.8 to 2.3 points. Mean MOCART score at follow-up was 58.3 points. Cartilage repair of patellar lesions aided by a retraction system in a dry arthroscopy setup is a promising approach. Further studies are needed to evaluate this procedure and compare it to existing matrix implantation techniques. The level of evidence for the study is 4 (case series).
Keywords: cartilage repair; knee; patella; AMIC; dry arthroscopy